Cardiorenal syndrome and diabetes: an evil pairing - Méndez Fernández, Ana Belén; Vergara Arana, Ander; Olivella San Emeterio, Aleix; Azancot Rivero, Maria Antonieta; Soriano Colome, Toni; Soler Romeo, Maria Jose (Frontiers in Cardiovascular Medicine, 2023)
Cardiorenal syndrome (CRS) is a pathology where the heart and kidney are involved, and the deterioration of one of them leads to the malfunction of the other. Diabetes mellitus (DM) carries a higher risk of HF and a worse prognosis. Furthermore, almost half of people with DM will have chronic kidney disease (CKD), which means that DM is the main cause of kidney failure. The triad of cardiorenal syndrome and diabetes is known to be associated with increased risk of hospitalization and mortality. Cardiorenal units, with a multidisciplinary team (cardiologist, nephrologist, nursing), multiple tools for diagnosis, as well as new treatments that help to better control cardio-renal-metabolic patients, offer holistic management of patients with CRS. In recent years, the appearance of drugs such as sodium-glucose cotransporter type 2 inhibitors, have shown cardiovascular benefits, initially in patients with type 2 DM and later in CKD and heart failure with and without DM2, offering a new therapeutic opportunity, especially for cardiorenal patients. In addition, glucagon-like peptide-1 receptor agonists have shown CV benefits in patients with DM and CV disease in addition to a reduced risk of CKD progression.